AN ANALYSIS OF THE THIRD SEMESTER STUDENTS’ ABILITY IN DEVELOPING NARRATIVE TEXT OF ENGLISH EDUCATION STUDY PROGRAM IN MUHAMMADIYAH UNIVERSITY OF METRO - Aulia Hanifah Qomar (Premise: Journal of English Education and Applied Linguistics, 2016)
An Analysis of The Third Semester Students’ Ability in Developing Narrative Text of English Education Study Program in Muhammadiyah University of Metro.Applied Linguistics Departement. English Education Study Program, Faculty of Education and Teacher Training in Muhammadiyah University of Metro.An analysis of The Third Semester Students’ Ability in Developing Narrative Text of English Education Study Program in Muhammadiyah University of Metro is the point because, the students worse in writing. They have many problems, actually writing genre and especially in narrative text. The purpose from this research is to analyze students’ ability in developing narrative text, and to know what the problem it happened to the students. The subjects of this research were the third semester of English education study program, and the sum of this subject was 36 students.This research used qualitative research. The data was collected by using questionnaire. The predicted research finding is the most valuable one that the students’ writing ability can be well, if we practice in our daily activity like make a story.